2016
DOI: 10.1515/ejthr-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Customer delight: perception of hotel spa consumers

Abstract: Delighted customers are those whose expectations have been exceeded by the service provider. Competitors in the hotel business need to go beyond what is expected in order to satisfy the guest with an unpredictable positive experience. This study was aimed to clarify the significance of customer delight as an antecedent to customer loyalty, in five-star hotel spas in Portugal. To better understand spa consumers' perception of delight, the development and testing of an integrated model was undertaken by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
1
13
1
6
Order By: Relevance
“…It can be beneficially obtained in a way to improve service quality as proven on the empirical researches (Lai, 2014;Lemy et al, 2019;Lin et al, 2016;Nguyen-Phuoc et al, 2020). Furthermore, service quality that is defined as consumers' perceptions as well as expectations before receiving services and, the means by which services are provided simultaneously , has very strong influence on (Al-Hawari, 2011;Elias-Almeida et al, 2016;Torres & Kline, 2006) and the very close relationship (Choi et al, 2019;Kao et al, 2016;Wattanakamolchai et al, 2016) with customer delight which has been proved in some research literature (Ahrholdt et al, 2016;Joudeh & Dandis, 2018;Wang, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…It can be beneficially obtained in a way to improve service quality as proven on the empirical researches (Lai, 2014;Lemy et al, 2019;Lin et al, 2016;Nguyen-Phuoc et al, 2020). Furthermore, service quality that is defined as consumers' perceptions as well as expectations before receiving services and, the means by which services are provided simultaneously , has very strong influence on (Al-Hawari, 2011;Elias-Almeida et al, 2016;Torres & Kline, 2006) and the very close relationship (Choi et al, 2019;Kao et al, 2016;Wattanakamolchai et al, 2016) with customer delight which has been proved in some research literature (Ahrholdt et al, 2016;Joudeh & Dandis, 2018;Wang, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Likewise, customer perceptions of different service dimensions affect overall delight (Oliver et al, 1997;Ahrhodt et al, 2017). This relationship was also supported by Elias-Almeida et al, (2016), which found that service quality in five-star hotel spas in Portugal had a positive impact on customer delight. Consequently: H3: The service quality dimensions will positively impact spa-goers' delight…”
Section: Joymentioning
confidence: 66%
“…The findings were congruent with Snoj and Mumel's (2002) and Lo et al, (2105) which found also that responsiveness and reliability were the most important two quality attributes for spa-goers. However, these four service quality predictors of delight were, noticeably, related to staff performance, which highlights the impact of the "people" aspect in the creation of customer delight in a spa settings, as in Elias-Almeida et al, (2016). This can be explained by the fact that spa is a very personal service where visitors' experience is typically influenced by the quality of interaction between the visitor and the staff.…”
Section: Discussion and Conclusion Effects Of Consumption Emotions Omentioning
confidence: 91%
See 2 more Smart Citations